2017
DOI: 10.1210/js.2017-00013
|View full text |Cite
|
Sign up to set email alerts
|

Increased Adrenal Androgens in Overweight Peripubertal Girls

Abstract: Context:Peripubertal hyperandrogenemia—a precursor to polycystic ovary syndrome—is prominent in girls with obesity.Objective:We examined sources of overnight testosterone (T) and progesterone (P4) and potential sources of obesity-associated hyperandrogenemia during puberty.Design:Cross-sectional.Setting:Research unit.Participants/Interventions:Fifty girls ages 7 to 18 years—both normal weight (NW) and overweight (OW)—underwent dexamethasone (DEX) suppression (1 mg orally; 10 pm) and cosyntropin stimulation tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Davio et al [ 24 ] found that 11-KT is the dominant circulating bioactive androgen during normal and premature adrenarche and that concentrations do not seem to decline in women as they age. Ovarian-derived testosterone is higher in peripubertal girls with obesity [ 25 ]. However, in premenarchal daughters of women with PCOS, 11-oxyandrogens were not elevated relative to age-matched controls [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Davio et al [ 24 ] found that 11-KT is the dominant circulating bioactive androgen during normal and premature adrenarche and that concentrations do not seem to decline in women as they age. Ovarian-derived testosterone is higher in peripubertal girls with obesity [ 25 ]. However, in premenarchal daughters of women with PCOS, 11-oxyandrogens were not elevated relative to age-matched controls [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that girls with obesity have relatively higher androgen levels and are consequently prone for an increased AS, which might have influenced the results. 36 However, we could only speculate on the theory, since no analysis stratified by sex was performed, since the number of participants assigned to a subgroup stratified by sex and Tanner stage was too small to analyze. In addition, the observed difference in BMI may have limited the influence of Tanner stage on AS.…”
Section: Discussionmentioning
confidence: 99%
“…19 The precise source of such T increases is unclear, but may be of adrenal origin early in puberty, with increasing ovarian contribution by mid to late puberty. 20 It has been recently recognized that 11-oxygenated C19 androgens—generated in part via aldo-keto reductase family 1 member C3 (AKR1C3) activity in the adrenal gland and adipose tissue—are important contributors to androgen excess in adolescent girls and women. Such androgens include 11-ketotestosterone (11-KT), which binds and activates the androgen receptor with the same affinity as T. 11-KT levels are elevated in girls with premature adrenarche, congenital adrenal hyperplasia (CAH), PCOS, and obesity.…”
Section: Defining Hyperandrogenemia In Adolescentsmentioning
confidence: 99%
“…79 By late puberty, girls with obesity demonstrate fourfold higher post-dexamethasone levels of free T and twofold higher A4 and free T responses to cosyntropin, suggesting both ovarian and adrenal contributions to obesity-associated hyperandrogenemia in later puberty. 20…”
Section: Obesity-related Hyperandrogenemiamentioning
confidence: 99%